Case reportAn unusual case of high cervical spinal cord injury - Velnar, Tomaz; Smrkolj, Vladimir; Cerovic, Ognjen; Pecaric Meglic, Nuska; Tauscher, Gloria (Folia Neuropathologica, 2010)
Isolated spinal cord injuries can rarely be found in patients with no traumatic radiological abnormalities of the spine. Stenoses of the medullary canal and degeneration of cervical spine are the predisposing factors. A case report of a 68-year-old patient is described, who developed quadriplegia with cardiac arrest due to isolated cervical spinal cord injury while jumping on a trampoline. Compressions of the spinal cord with intramedullary and epidural haemorrhage between vertebrae C3 and C6 were observed with no traumatic radiological abnormalities of the spine skeleton.